2019
DOI: 10.1159/000501903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postoperative Delirium: Validity and Reliability of the Nursing Delirium Screening Scale in the Turkish Language

Abstract: KeywordsNursing personnel · Delirium of mixed origin · Reliability · Validity Abstract Purpose: Postoperative delirium is the most well-known form of postoperative cognitive impairment in all patient groups, especially in the elderly. Delirium is a syndrome that causes serious consequences, increasing mortality and morbidity rates and extending the length of hospital stay. The aim of this study was to evaluate the validity and reliability of the Turkish version of the Nursing Delirium Screening Scale (Nu-DESC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 37 publications
0
23
0
3
Order By: Relevance
“…A total of 4290 studies were screened on the title/abstract. Eventually, 47 studies were assessed full text, of which 27 excluded: delirium diagnosis not reproducible (n s (number of studies) = 9), [20][21][22][23][24][25][26][27][28] full text not found (n s = 3), [29][30][31] duplicate (n s = 3), [18,32] paediatric patients (n s = 1) [33], overlapping populations (n s = 3), [4,34,35] no delirium assessment (n s = 1), [36] no original data (n s = 2) [37,38] and an unclear number of patients undergoing intracranial surgery (n s = 5) [39][40][41][42][43]. Finally, 20 paper were included in the qualitative analysis and 18 papers in the quantitative analysis (n p (number of patients) = 5083).…”
Section: Systematic Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4290 studies were screened on the title/abstract. Eventually, 47 studies were assessed full text, of which 27 excluded: delirium diagnosis not reproducible (n s (number of studies) = 9), [20][21][22][23][24][25][26][27][28] full text not found (n s = 3), [29][30][31] duplicate (n s = 3), [18,32] paediatric patients (n s = 1) [33], overlapping populations (n s = 3), [4,34,35] no delirium assessment (n s = 1), [36] no original data (n s = 2) [37,38] and an unclear number of patients undergoing intracranial surgery (n s = 5) [39][40][41][42][43]. Finally, 20 paper were included in the qualitative analysis and 18 papers in the quantitative analysis (n p (number of patients) = 5083).…”
Section: Systematic Searchmentioning
confidence: 99%
“…Two RCTs, seven prospective and eleven retrospective cohort studies were included. Disease type for patients undergoing intracranial surgery were categorized in mixed (33.9%, n p = 1478), [4,10,21,32,39,[41][42][43][44][45][46][47][48] functional neurosurgery (26.8%, n p = 552), [11,46,[49][50][51] neurovascular (10.5%, n p = 145), [52][53][54] neuro-oncology (18.4%, n p = 1969) [5,7,55], traumatic brain injury (TBI) (4.3%, n p = 27) [56,57] and microvascular decompression (MVD) (6.2%, n p = 912) [9]. The mixed group included neurovascular, neuro-oncologic, TBI or hydrocephalus operations and functional neurosurgery (solely deep brain stimulation (DBS) in patients with Parkinson's disease).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Her madde 3 puanlık bir ölçekte (0-2) derecelendirilmekte ve toplam puan 0-10 arasında değişmektedir. Deliryum için eşik değerin 2 olduğu bildirilmektedir 4,33,34 . Ölçeği tamamlamak yaklaşık 1 dakika sürmektedir 4 .…”
Section: Deliryumu Taramaya Yönelik Araçlarunclassified
“…NuDESC'in deliryum tanısı için %85.7 duyarlılığa ve %86.8 özgüllüğe sahip olduğu gösterilmiştir 32 . Ölçek ülkemize Çınar ve Aslan tarafından kazandırılmış olup, duyarlılığı 92.27, özgüllüğü ise 92.72 olarak belirlenmiştir 34 .…”
Section: Deliryumu Taramaya Yönelik Araçlarunclassified